Designing Grammar Video for Beginner Level - Luluk Choirun Nisak Nur; Izzatul Abidah; Nurul Afidah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The ability of lecture to understand and teach with the technology greatly affects to the students' abilities in their learning process. By developing technology, it can improve the quality of education. Therefore, the researchers aimed to design the learning media for students in the first semester in University level. This research is designing learning media through Grammar Video to learn English Grammar in writing skills at the university levels. This research use Research and Development (R&D) method and through ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. This learning media called as GraVid (Grammar Video). This learning media is a video designed to develop products in order to test feasibility as an alternative learning media that can help students understand English Grammar in writing skills. The research instrument is an interview with English lecture’s and also distribute questionnaire on the first semester, Biology class students of the faculty of education in KH. Abdul Wahab Hasbulloh University that contains of 15 students as a sample. The results of this study show that: (1) the results of the media expert score are 4. (2) The results of the material expert score are 3.36 (3) the results of the product test to the students are 4.08. Researcher concluded that English Grammar Video (GraVid) is suitable to use in Grammar learning process in the classroom. From these results, there suggestion that product is revised as suggested from the expert. . Keywords: Writing skill, Grammar Video, Learning Media.